2015
DOI: 10.1002/jhbp.275
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implication of serum carcinoembryonic antigen and carbohydrate antigen 19-9 for the prediction of malignancy in intraductal papillary mucinous neoplasm of pancreas

Abstract: Serum CA19-9 is significantly higher in patients with malignant IPMN, especially in patients with invasive and main duct type IPMN. The diagnostic power of serum CA19-9 in predicting malignancy is comparable to that of MPD >5 mm and mural nodules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 23 publications
3
46
0
Order By: Relevance
“…International Consensus Guidelines published in 2012 suggested several features indicative of malignant transformation, including the dilatation or calibre change in MPD, large cysts, mural nodules and septal wall thickening. In 2017, the guidelines added raised serum carbohydrate antigen (CA) 19‐9 level as a worrisome feature, based on studies that showed a relationship between high CA 19‐9 levels and malignant IPMN. The guidelines recommended careful surveillance or resection of IPMN with these features.…”
Section: Introductionmentioning
confidence: 99%
“…International Consensus Guidelines published in 2012 suggested several features indicative of malignant transformation, including the dilatation or calibre change in MPD, large cysts, mural nodules and septal wall thickening. In 2017, the guidelines added raised serum carbohydrate antigen (CA) 19‐9 level as a worrisome feature, based on studies that showed a relationship between high CA 19‐9 levels and malignant IPMN. The guidelines recommended careful surveillance or resection of IPMN with these features.…”
Section: Introductionmentioning
confidence: 99%
“…Of these studies, 33 investigated mural nodules5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 21 examined dilatation of the main pancreatic duct (MPD)7 9, 15 16, 18 21, 23 26, 27 30, 32 36, 38, 39, 40, 41, 42, 43, 44, 45, 46, 21 analysed cyst size5 7, 8, 9 14, 15 18, 20 23, 25 27, 28 31, 36 38, 40 41, 43 47, 48, 49, 17 assessed CA19‐9 increase14 …”
Section: Resultsmentioning
confidence: 99%
“…Data from our institution [35] indicate that serum CA 19-9 in patients with resected BD-IPMN is useful for detecting invasive carcinoma (AUC 0.68; 95% CI 0.52-0.84) but not for detecting HGD without invasive carcinoma (AUC 0.54; 95% CI 0.42-0.67). Importantly, a cutoff of 100 units/ml had the highest accuracy for detecting invasive carcinoma (93%), compared with the more commonly used cutoff of 37 units/ ml (83%) [36,37]. Elevated serum CA 19-9 has now been included as a worrisome feature in the revised IAP 2012 Fukuoka consensus guidelines [10]; while our experience would support this addition, we must keep in mind that its utility appears to be restricted to detecting invasive carcinoma (and not HGD), and the optimal cutoff value may still need to be determined.…”
Section: Circulating Biomarkers For Prediction Of High-risk Intraductmentioning
confidence: 99%